A new curriculum model for second-level physical education: Y-PATH PE4Me. Issue 2 (4th May 2022) - Belton, Sarahjane; O'Brien, Wesley; Murtagh, Elaine; Costa, Joao; Issartel, Johann; McGann, Jamie; Manninen, Mika
ABSTRACT: In Ireland, physical education (PE) in the first three years of second level (12–15 years) is taught within the broader program area of Wellbeing, which necessarily influences the aims and objectives which need to be achieved. Within this context, Y-PATH PE4Me is proposed as an underpinning curriculum model to serve as an appropriate and valuable guide to aid delivery of second-level PE. Y-PATH PE4Me aims to enable every student to lead a sustained physically active life. This proposed curriculum model is facilitated by (i) utilising pedagogical strategies to foster an autonomous motivational climate, and (ii) maintaining a consistent focus on core learning outcomes, which emphasise the development of positive attitudes and motivation towards physical activity, health-related knowledge and awareness, and core movement skills. Y-PATH PE4Me offers a structured model to guide well-aligned pedagogical decisions towards the goals and philosophy of wellbeing-aligned PE.